Serviços em supermercados : o que os clientes e gerentes percebem? - Araújo, Leandro Condeixa (2016)
The Brazilian supermarket sector is booming, and was responsible in 2015 for approximately 5.3% of the Brazilian GDP and employing about 4 million people across the country, directly or indirectly. With this growth scenario, prosperity and strength of the supermarket sector, could be expected that their services were considered at least satisfactory for consumers, which, apparently, is not reflected in reality. This study aimed to seek to understand how customers and supermarket managers understand the quality of services provided by front-line staff, by comparing the position of both groups of subjects regarding the studied phenomenon, and deepening understanding of the dimensions of quality services in supermarkets. A review was carried out in the literature available about the related issues and to achieve work objectives carried out a qualitative research through interviews with customers and supermarket managers, looking in detail to understand their understanding of the quality of services provided by employees front line through the intersection of the results of both groups of subjects. As a result, we have identified one hundred and fifty quality items that the customer perceives as a reflection of the work of the supermarket front-line staff and we compare them with the understanding of the managers who performed quite similarly. With these identified items we could go a little deeper understanding of the dimensions of service quality in supermarkets, realizing a highlight to tangibility, communication, trust / reliability and courtesy.